Employment retention after moderate-severe traumatic brain injury (TBI) in the British Army 1989–98. Issue 5 (16th April 2004) - McLeod, A; Wills, A; Etherington, J
Abstract : Aims: To examine retention in employment of subjects with moderate-severe traumatic brain injury (TBI) in the British Army. Methods: Comparative groups study of retention in Army employment after TBI using 564 TBI, 368 lower limb fracture, and 25 575 healthy subjects. Kaplan-Meier survival analysis was used to examine, stratifying for age, continuation in Army employment for six years after TBI. Results: Subjects in the younger groups (mean ages 23 years and 27 years respectively) with either TBI or lower limb fracture remained in employment longer than healthy peers (median time for TBI, 3.91 years, lower limb fracture, 4.39 years, and healthy, 1.74 years). This trend changed through age stratification and for older subjects the reverse pattern was seen. In group 4 (mean age 41 years), median retention time for TBI was 3.33 years, for lower limb fracture, 3.75 years, healthy 5.55 years. Older subjects also showed a marked drop out rate at one year after injury; 32.7% of those with TBI in group 3 (mean age 31 years) had left Army employment at the end of year one compared with 19% in age group 1 (mean age 23 years). Conclusions: Younger soldiers with either TBI or lower limb fracture are retained in Army employment longer than their healthy peers. This may be due to sheltered employment, the availability of ongoing support, or transience of the healthy population. Since these results were drawn from incidence data on moderate and severe TBI it may be that those who serve on after TBI will do so with some degree of disability which affects occupational performance. There may be a significant unmet rehabilitation need for this group which is the focus of ongoing research.